Γ-MnS films with 3D microarchitectures: comprehensive study of the synthesis, microstructural, optical and magnetic properties12. Issue 5 (8th January 2018) - Dhandayuthapani, T.; Girish, M.; Sivakumar, R.; Sanjeeviraja, C.; Gopalakrishnan, C.; Nagarajan, R. S.; Mathew, S.; Jun, Ding; Venkatesan, T.; Kalai Selvan, G.; Manikandan, K.; Arumugam, S.
Abstract : A simple procedure to synthesize 3D microarchitectures of γ-MnS films at low temperature is described in the present work. Abstract : In the present work, for the first time, we report γ-MnS films with a 3D microsphere morphology prepared through a chemical bath deposition technique at low temperature under aqueous conditions. The X-ray diffraction study confirmed the formation of wurtzite phase γ-MnS. Growth temperature induces a change in the morphology of γ-MnS films from microspheres to microflakes, which may be due to the difference in the nucleation process. The obtained γ-MnS microspheres have a surface area of ∼25 m 2 g −1 . The photoluminescence spectra show a strong yellow emission band centered at about 550 nm. The obtained microsphere ensemble plays a crucial role in influencing the magnetic behavior of γ-MnS films. The highest coercive field (3320 Oe) and saturation magnetization (17 emu g −1 ) were obtained for γ-MnS microspheres prepared at 60 °C.